AN ANALYSIS OF FIGURATIVE LANGUAGE IN NOVEL PAPER TOWNS BY JOHN GREEN - Melly Melly; Evert H. Hilman (IKIP Siliwangi, 2022)
The objective of this research is to identify the types of figurative language and the translation procedures applied in the translation as well as to find out the translation quality assessment based on Newmark’s and Nababan et al’s theories. Descriptive qualitative research is the method used in this study. The result shows that there are 100 sentences that have figurative language, they are :metaphor 21%, hyperbole 25%, simile 34%, personification 18%, and idiom 2%. The translation procedures includes compensation 18%, expansion 8%, through-translation 39%, naturalization 1%, transference 8%, synonymy 9%, and transposition 17%. Finally, the outcome of the translation quality assessment indicate that 1 data is less accurate, less acceptable. Whilst, 2 less readable. The rest of the translation are accurate, acceptable, and readable. Keywords: Figurative Language, Translations, Newmark, Translation Quality Assessment